Interfacial Properties and Foamability of Amphiphilic Molecules - Stella Widyaningtyas; Audrey Drelich; Isabelle Pezron (Institut Teknologi Sepuluh Nopember, 2015)
Surface-active molecules are widely used in industry. Triton X-100, sodium lauryl ether sulfate, sodium dodecyl sulfate and bovine serum albumin are commonly used in daily products. They can form foams because of adsorption phenomena at the surface. Each molecule has its own characteristic and foaming ability. This research deals with relation between interfacial properties and foamability by using three different methods: the Wilhelmy plate method to verify the CMC value, the maximum bubble pressure to determine dynamic surface tension, and the Bikerman method to assess the foamability. Interfacial properties and foamability will be studied and the difference observed between surfactant and protein will be discussed.